Benefits of Oli-Ola and Pycnogenol Extracts in the Treatment of Melasma: Benefits of Oli-Ola and Pycnogenol Extracts in the Treatment of Melasma - Martins, Mariana Marri; Ceranto, Daniela de Cassia Faglioni Boleta; Jacomassi , Ezilda; Lourenço, Emerson Luiz Botelho; Cogo, Juliana; Rosa, Simony Rodrigues Bernardelli; Colombo, Eliane Franco; Cebrian, Rosinéia Aparecida Vilela; Andrzejewski, Luciana; Zardeto, Giuliana (RCMOS - Revista Científica Multidisciplinar O Saber, 2025)
The pathology of melasma is a chronic acquired hypermelanosis located in the skin of a little-known cause. It may be influenced by several factors that contribute to the appearance of lesions, such as exposure to solar radiation, use of contraceptives, hormonal disorders, and gestational period. There is no cure for this hypermelanosis, but there are treatments and preventions that can soften the spots. Studies have shown the efficiency of using natural antioxidants such as Oli-Ola and pycnogenol to prevent and treat melasma for numerous benefits to the body. Therefore, this study aimed to demonstrate, through a literature review, the benefits of the natural extracts Oli-Ola and pycnogenol in the treatment of melasma. For this, a bibliographic survey was carried out at Google academic and Pubmed databases, where scientific articles published between the years 2014 and 2024 were selected. According to the analyzed studies, the natural extracts Oli-Ola and pycnogenol have antioxidant, anti-inflammatory actions and prevent skin aging. Oli-Ola acts as a cholesterol regulator and anti-hypertensive; it increases the immune system, has peeling action in capsules that stimulates collagen production, acts on firmness and elasticity of the skin, and acts as a depigmenting agent, leaving the skin tone more uniform. Pycnogenol assists in improving skin health. It protects collagen and elastin, is antimicrobial, a natural photoprotector, and is anti-photoaging. Therefore, using natural activities appears as an alternative for the treatment of melasma, requiring more research on their application potential.